Genotyping of Porcine Endogenous Retroviruses from a Family of Miniature Swine - Quinn, Gary (American Society for Microbiology, 2004)
The identification of animals in an inbred miniature swine herd that consistently fail to produce replication- competent humantropic porcine endogenous retrovirus (PERV) has prompted studies on the biology of PERV in transmitter and nontransmitter animals. We analyzed PERV RNA transcript profiles in a family of inbred miniature swine (SLA(d/d) haplotype) in which individual members differed in their capacity to generate humantropic and ecotropic (i.e., pigtropic) virus. We identified unique HaeIII and HpaII gag restriction fragment length polymorphism (RFLP) profiles resulting from single nucleotide polymorphisms in blood cells; these were found only in animals that produced humantropic PERV. These HaeIII and HpaII gag RFLP profiles proved to be components of humantropic PERV as they were transmitted to 293 human target cells in vitro. The humantropic HaeIII and HpaII gag RFLP genotypes in the family of study were not present in other miniature swine in the herd that produced humantropic PERV, indicating that these RFLP profiles relate specifically to this family's lineage.